Hydrogen SWOT Analysis of Poland’s Energy Transition - Paweł Brusiło; Adam Węgrzyn; Andrzej Graczyk; Alicja Małgorzata Graczyk (Energies)
This paper presents a comprehensive SWOT (strengths, weaknesses, opportunities, and threats) analysis of utilizing hydrogen as a renewable fuel of non-biological origin (RFNBO) in Poland’s energy transition. Given Poland’s reliance on fossil fuels, its deep decarbonization poses socio-economic and infrastructural challenges. This study examines the strengths, weaknesses, opportunities, and threats associated with integrating hydrogen as an RFNBO fuel into Poland’s energy mix, focusing on economic, regulatory, technological, and social factors. The strengths identified include potential energy independence from fossil fuels, increased investment, and hydrogen’s applicability in hard-to-abate sectors. Weaknesses involve a low share of renewable hydrogen in the energy mix and the need for infrastructure development. Opportunities arise from European Union policies, technological advancements, and global trends favoring renewable hydrogen adoption. Threats encompass high production costs, regulatory uncertainties, and competition from other energy carriers. The analysis concludes that while hydrogen as an RFNBO fuel offers potential for decarbonizing Poland’s energy mix, realizing this potential requires large-scale investments, a supportive regulatory framework, and technological innovation.